Simple Harmonic Motion Conceptual Mastery in Online Multimedia Assisted Guided Inquiry Learning - Hawin Marlistya Priswayani; Sentot Kusairi; Nandang Mufti (Pascasarjana Universitas Negeri Malang (UM), 2021)
Abstract: This study aims to analyze the students’ mastery concepts of Simple Harmonic Motion on Guided Inquiry learning assisted by online multimedia. The study involved 36 students of class X natural science of SMA Negeri 4 Jember. A multiple-choice test was used to measure mastery concepts and was conducted before and after learning. The data obtained were then analyzed using a mixed-method with an embedded experiment design. The results showed that the increase in students' concept mastery was influenced by the guided inquiry learning model assisted by online multimedia. Based on the effect size value, the learning carried out has an effect on the strong effect category. The average increase in students' mastery of concepts is in the high category.Abstrak: Penelitian ini bertujuan untuk menganalisis peningkatan penguasaan konsep siswa pada pembelajaran guided inquiry berbantuan multimedia online. Penelitian ini melibatkan 36 siswa kelas X IPA SMA Negeri 4 Jember. Tes pilihan ganda beralasan digunakan untuk mengukur skor penguasaan konsep siswa serta dilakukan sebelum dan setelah pembelajaran. Data kuantitatif dan kualitatif yang diperoleh selanjutnya dianalisis menggunakan mixed method dengan desain embedded experiment. Hasil penelitian menunjukkan bahwa peningkatan penguasaan konsep siswa dipengaruhi oleh model pembelajaran guided inquiry berbantuan multimedia online. Berdasarkan nilai effect size, pembelajaran yang dilakukan memberikan efek pada kategori strong effect. Rata-rata peningkatan penguasaan konsep siswa berada pada kategori tinggi.